Customer service - Henry, Michael; Collins, Cath; Video Education Australasia (Victoria : Video Education Australasia, 2007)
This program focuses on both internal and external customers and clients using a fictional current affairs show on this day and its presenter Naomi Henderson as a case study
Title from container
Executive producer : Mark McAuliffe ; senior producer : Richard Leigh ; editor : Michael Henry ; camera : Peter Zakharov
Voice over : Chelsea Bruland
Keywords: Customer services; Customer relations